2002
DOI: 10.1238/physica.regular.065a00502
|View full text |Cite
|
Sign up to set email alerts
|

Envelope Solitons versus Solitons

Abstract: A theory involving a correspondence between envelope solitonlike solutions of the generalized nonlinear Schro« dinger equation (GNLSE) and solitonlike solutions of the generalized Korteweg^de Vries equation (GKVdE) is developed within the context of the Madelung's £uid description (£uid counterpart description of the GNLSE). This correspondence, which, under suitable constraints, can be made invertible, seems to be very helpful for ¢nding one family of solutions (whether envelope solitonlike solutions of the G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
158
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(159 citation statements)
references
References 9 publications
0
158
0
1
Order By: Relevance
“…Thus, these plasma parameters are significantly controlled the stability conditions of the HIAWs. If P Q < 0, HIAWs are modulationally stable and for the case P Q > 0, HIAWs are modulationally unstable against external perturbations [37][38][39][40] and simultaneously when P Q > 0 and k MI < k c , the growth rate (Γ g ) of MI is given [41] by…”
Section: Stability and Rogue Wavesmentioning
confidence: 99%
“…Thus, these plasma parameters are significantly controlled the stability conditions of the HIAWs. If P Q < 0, HIAWs are modulationally stable and for the case P Q > 0, HIAWs are modulationally unstable against external perturbations [37][38][39][40] and simultaneously when P Q > 0 and k MI < k c , the growth rate (Γ g ) of MI is given [41] by…”
Section: Stability and Rogue Wavesmentioning
confidence: 99%
“…When P Q > 0, the DAWs are modulationally unstable against external perturbation (bright envelope solitons exist) and on the other hand when P Q < 0, the DAWs are modulationally stable (dark envelope solitons exist) [28,29,27,31]. simultaneously when P Q > 0 and k M I < k c , the growth rate (Γ g ) of MI is given [30] by…”
Section: MImentioning
confidence: 99%
“…This modulation instability mechanism is tantamount to the well-known Benjamin-Feir instability in hydrodynamics. Furthermore, the modulation instability is related to the occurrence of localized envelope structures (solitons) of various kinds [37][38][39]. For the unstable wave packet (P Q > 0), it can be shown that the QIA solitary waves propagate as an envelope soliton.…”
Section: Stability/instability Of Planar Envelope Pulsementioning
confidence: 99%
“…The wave amplitude is inversely proportional to |Q|, and the wave width is proportional to |P |. For an extensive list of a number of envelope soliton solutions of the NLSE of the bright or dark (black/grey) type, the reader may consult references [38,39]. We have chosen our physical parameters to be applicable for white dwarfs.…”
Section: Stability/instability Of Planar Envelope Pulsementioning
confidence: 99%